UUM chosen as Tan Chong Centre of Asian Management Studies HQ - Malaysian, Reserve (Malaysian Reserve, 2012)
TAN CHONG Gruop (TCG) has chosen Universiti Utara Malaysia (UUM) as the headquarters for its academic center, Tan Chong Center of Asian Management Studies.